HUBUNGAN PROMOSI, HARGA, DAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN HIJAB PASHMINA SECARA ONLINE (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Universitas Islam Malang - Dewi Milati Mukarromah; M. Hufron; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2017)
This study aims to determine the relationship promotions, prices and products simultaneously on purchasing decisions online pashmina scarf. The population in this study were students from poor Islamic university economic faculties from generation 2013 to 2015 the number of samples taken by 83 respondents and methods used in sampling using purposive sampling. The data collection technique used was a questionnaire. So the conclusion from this study that all these variables have a relationship together against the consumer's decision to purchase online pashmina scarf because it has multiple correlation (R) of 0.529.